2017
DOI: 10.1186/s12909-016-0853-4
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of mistreatment among trainees vary at different stages of clinical training

Abstract: BackgroundMistreatment of trainees remains a frequently reported phenomenon in medical education. One barrier to creating an educational culture of respect and professionalism may be a lack of alignment in the perceptions of mistreatment among different learners. Through the use of clinical vignettes, our aim was to assess the perceptions of trainees toward themes of potential mistreatment at different stages of training.MethodsBased on observations from external experts embedded in the clinical learning envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 26 publications
(37 reference statements)
1
25
3
2
Order By: Relevance
“…during training, which is similar to reported percentages among general surgery residents, nonsurgical medical trainees, and nonmedical professionals. [22][23][24][25] In a recent study by McKinley et al 11 that surveyed general surgery, medicine, and anesthesia residents across two institutions, rates of GBDB ranged from 30% to 36% across the three specialties, which is slightly lower than the 38% we found. In this manuscript, GBDB was the most commonly cited negative workplace experience among female integrated residents, and the perceived consequences were meaningful.…”
Section: Discussioncontrasting
confidence: 71%
“…during training, which is similar to reported percentages among general surgery residents, nonsurgical medical trainees, and nonmedical professionals. [22][23][24][25] In a recent study by McKinley et al 11 that surveyed general surgery, medicine, and anesthesia residents across two institutions, rates of GBDB ranged from 30% to 36% across the three specialties, which is slightly lower than the 38% we found. In this manuscript, GBDB was the most commonly cited negative workplace experience among female integrated residents, and the perceived consequences were meaningful.…”
Section: Discussioncontrasting
confidence: 71%
“…Residents are expected to be professionals and develop an altruistic attitude towards their patients and colleagues and are often expected to take on the responsibilities of autonomous physicians. Yet it is also recognized that residents and fellows are a group that requires special protections, such as the Accreditation Council of Graduate Medical Education’s (ACGME) 80-h limit [ 8 ], as without such protections trainees may be taken advantage of or mistreated [ 9 ]. Trainees also lack privileges attained by post-graduate physicians such as financial compensation or ability to negotiate, or flexibility with job requirements, mandatory attendance of didactics, and limited availability of sick leave or child-care.…”
Section: Competence Vs Identitymentioning
confidence: 99%
“…The authors also reported an adjusted odds ratio for burnout associated with any mistreatment of 1.98 (95% confidence interval [CI] 1.62, 2.42]. Kulayat et al 54 have suggested that perceptions of mistreatment vary along the duration of medical training, implicating clinical rotations in the indoctrination of students on the prevailing culture.…”
Section: Provision Of Servicementioning
confidence: 99%